Fonologi Bahasa Arab (Tinjauan Deskriptif Fonem Bahasa Arab) - Amrulloh, Muhammad Afif (Universitas Islam Negeri Raden Intan Lampung, 2016)
Language as an object of linguistics studies has an important role in human life. Language and life is a phenomenon that can’t be released like two sides of a coin. Language is a symbol of sounds system arbitrarily used by humans to communicate between each other. As a system, the language has a systematic nature (berkaedah) and systemic (bersubsistem). One of the subsystems is phonology. Phonology as one field or level of study in linguistics were discussed related to everything about language sounds. The language sounds are categorized into two, namely phonetic and phonemic. Phonetics as a branch of phonology discusses relevant language sounds without affecting the meaning, while discussing about the sounds of language phonemes that affect meaning. This paper would like to study about the Arabic language phonology, in particular on phonemic. This study included within the scope of the al-Aswa> t, which is the science deals with the narrative of the language sounds, movement and acceptance. Before studying how to prepare the structure of a language and its meaning and so on, then it must first be familiar with the sounds of the language in it. Sounds of language that are must be known in advance for language learners (Arabic learners). Therefore, phonology becomes important to study in learning and language acquisition (foreign language). Thus, it becomes very important to understand the study of phonology or al-Aswa> t, in order to obtain a comprehensive understanding associated Arabic language sounds, which certainly every sound has its own meaning